Assessment of the Role of Private Schools in the Development of Education in Ghana, A Study of the Kumasi Metropolis (Journal of Science and Technology, 2016)
Increased demand by the people and the limited resources available to the government have made it difficult for the government alone to finance education provision in the country. It has therefore become increasingly necessary for the private sector to get involved in the provision of educational facilities in the country.This study sought to capture the contribution that the private sector is making to supplement the efforts of the government to improve the basic education system in the country. It established that private schools are contributing greatly to the development of education in the Kumasi Metropolis and by implication, the country. These include the fact that, private schools outnumber public schools from the Primary to the Senior Secondary level, they enroll more pupils and students, they also employ more teachers, most significantly more untrained female teachers, and they perform better in examinations than the public schools.The above not withstanding, private schools, like public schools, have their own problems which include inadequate funds, poor infrastructure and high number of untrained teachers. Among the recommendations are that the government should make it possible for the private schools to benefit from the GETFund to enable them to address their financial problems; that Metropolitan, Municipal and District Assemblies should establish more public basic schools to help expand their coverage; and that the Ministry of Education should put in place mechanisms for the effective supervision of public basic schools to help improve their academic performance and thus make them more attractive.